2009
DOI: 10.1111/j.1348-0421.2009.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of OprD sequence and correlation with antimicrobial activity of carbapenem agents in Pseudomonas aeruginosa clinical isolates collected in Japan

Abstract: A total of 99 clinical isolates of metallo-ß-lactamase-negative Pseudomonas aeruginosa collected in Japan between 1998 and 2001 were studied for their susceptibilities to carbapenem agents and corresponding oprD gene mutations. The OprD sequence of each strain was grouped into two major classes, based on the pattern of alterations. Eighty strains (80.8%) were so-called 'full length type', whose OprD proteins were fully encoded. The remaining 19 strains (19.2%) were so-called 'defective type', which possessed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…AY553333). Moreover, we found that mutational inactivation of the oprD gene was a major determinant of resistance to imipenem, as previously described (2), and SDS-PAGE confirmed the absence of the protein in isolates whose oprD gene was not detected by PCR, as well as in isolate 37, which had a 15-nucleotide deletion, as previously described (15). We report here the first case of cooccurring bla VIM-2 and oprD porin loss in identical isolates of P. aeruginosa.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…AY553333). Moreover, we found that mutational inactivation of the oprD gene was a major determinant of resistance to imipenem, as previously described (2), and SDS-PAGE confirmed the absence of the protein in isolates whose oprD gene was not detected by PCR, as well as in isolate 37, which had a 15-nucleotide deletion, as previously described (15). We report here the first case of cooccurring bla VIM-2 and oprD porin loss in identical isolates of P. aeruginosa.…”
supporting
confidence: 86%
“…Nine strains harbored the IS element ISPa1328 inserted in OprD nucleotide position 419. This IS element was also described in P. aeruginosa in the United States (14), China (3), and Japan (15). This IS can be present in a different OprD location, as described previously (3).…”
mentioning
confidence: 99%
“…1A). Previously, porin was shown to be related to imipenem and carbapenem resistance (42,43). It is currently unclear why the vesicles from WT PAO1 caused more cytotoxicity to alveolar epithelial cells than did those from PAO1-⌬lasR (Fig.…”
Section: Fig 4 Lysed P Aeruginosamentioning
confidence: 99%
“…In some cases, antibiotic-resistant strains display a complete loss of one or more porins. For example, a lack of the basic amino-acid-selective outer membrane porin OprD in P. aeruginosa carbapenem-resistant clinical isolates can be due to a point mutation leading to an early termination of translation, a deletion, or the presence of an insertion element within the porin-encoding gene (218,261) or can be due to regulatory mutations (110,187). Point mutations in the promoter region that result in a lower level of transcription are another cause of porin loss.…”
Section: Resistance Due To Mutations In Porin-encoding Genesmentioning
confidence: 99%